UWEC [AND] the Selma-Eau Claire Domestic Intercultural Immersion ASB : An Exploration of the Impacts of High-Impact Practices on Blugold Attitudes Surrounding EDI Initiatives & Strategic Guidepost Goals - Jandrt, Jenna; Schultz, Nicole J.; Nesja, Joshua (My University, 2017)
As a campus with a current Strategic Guidepost Goal of working toward a student body that includes 20 percent enrollment of students of color and closing the opportunity gap, UWEC recognizes potential implicit biases inherent within institutional practices at UWEC that need to be addressed (Schmidt, 2015). This research explores student experiences with the Selma-Eau Claire Exchange Alternative Spring Break (ASB) trip, a university-supported Domestic Intercultural Immersion (DII) experience. The primary purpose of this high-impact experience is to expose Blugolds to history, activism, and nation-wide community partnerships, which intentionally work to support Equity, Diversity, and Inclusivity (EDI) initiatives on campus. Conclusions and implications exemplify the significance of DII ASB trips in supporting the development, implementation, and embracing of EDI initiatives to impact organizational culture on campus, assessed and contextualized utilizing tenets of Social Judgment Theory (Griffin, 2006).
Color poster with text, photographs, and graphs.
Keywords: Cultural competence; Domestic intercultural immersion; Selma-Eau Claire Exchange Alternative Spring Break (Eau Claire, Wis.); Posters